Droplet visualization in FlowVision - Fedorov A.А. (Numerical Methods and Programming (Vychislitel’nye Metody i Programmirovanie), 2018)
A method for the droplet visualization in FlowVision is proposed. FlowVision uses a local adaptive parallelepiped computational grid with subgrid geometry resolution. The VOF function is used to reconstruct the fluid and droplet surfaces which are then rendered using OpenGL. A number of approaches to improve the rendering of droplets are described. The effects of light refraction and light attenuation are considered.